Current practice of colonoscopy surveillance in patients with lynch syndrome: A multicenter retrospective cohort study in Japan. Issue 1 (1st November 2022) - Miyakura, Yasuyuki; Chino, Akiko; Tanakaya, Kohji; Lefor, Alan Kawarai; Akagi, Kiwamu; Takao, Akinari; Yamada, Masayoshi; Ishida, Hideyuki; Komori, Koji; Sasaki, Kazuhito; Miguchi, Masashi; Hirata, Keiji; et al.
Abstract: Objectives: Colonoscopy surveillance reduces the incidence of colorectal cancer through the detection and endoscopic removal of adenomas. Current guidelines recommend that patients with Lynch syndrome should have colonoscopy surveillance every 1–2 years starting at the age of 20–25. However, insufficient data are available to evaluate the quality and safety of colonoscopy surveillance for patients with Lynch syndrome nationwide in Japan. Methods: Patients with Lynch syndrome ( n  = 309) from 13 institutions who underwent one or more colonoscopy procedures were enrolled in this retrospective analysis. Colonoscopy completion rate, colonoscopy‐related complication rate, proportion with an adequate colonoscopy interval, and adenoma detection rate were reviewed. Results: The colonoscopy completion rate was 98.8% and a history of previous colorectal cancer surgery was significantly associated with a higher completion rate. All complications were associated with endoscopic treatment and the rate of bleeding needing hemostasis and perforation needing surgical repair were both 0.16% after colonoscopy with polypectomy. The adenoma detection rate at the first colonoscopy was 25%. Although there was no difference in the completion and complication rates based on differences in the colonoscopy experience of the endoscopist, the detection rate of adenomas and intramucosal cancers was significantly higher with more experienced endoscopists. The proportion of patients developing cancer was significantly higher with a >24 months than a ≤24 months interval. Conclusion: High‐volume experienced endoscopists and appropriate surveillance intervals may minimize the risk of developing colorectal cancers in patients with Lynch syndrome.